Caracterização e efeito do complexo de inclusão contendo óleo essencial de Eplingiella fruticosa (Lamiaceae) em β-ciclodextrina sobre a dor crônica musculoesquelética em roedores - Melo, Allan John de Oliveira (2018)
Eplingiella fruticosa (Lamiaceae) is an important aromatic medicinal herb traditionally used in northeastern Brazil for the treatment of pain, inflammation and convulsion. However, the scientific evidence of these activities has been little explored. Studies using essential oils (EOs) complexed with β-cyclodextrin (βCD) have shown promise for improving the biological effects of EOs in the management of chronic pain. Thus, the goal of the present study was to evaluate the antihyperalgesic effect of the essential oil obtained from E. fruticosa (EplEO) and its inclusion complex with βCD (EplEO-βCD) about chronic musculoskeletal pain in rodents. EplEO was extracted by hydrodistillation and its chemical composition was determined by gas chromatography coupled to mass spectrometry and flame ionization detector (GC-MS/FID). The EplEO-βCD complexes were prepared by two different methods (physical mixing and past complexation) and later characterized in differential scanning calorimetry, thermogravimetry / derivative thermogravimetry, moisture determination and scanning electron microscopy. After approval of the project by CEPA-UFS (Number 65/09) the FM model was induced in adult male albino Swiss mice by two injections of saline solution pH 4.0 (20 μl) in the left gastrocnemius, with a 5-day interval. After induction of hyperalgesia, the mice were treated daily (6th day to day 12) with EplEO (50 mg/kg, p.o.), EplEO-βCD (50 mg/kg, p.o.), vehicle (isotonic saline, p.o.) or Tramadol (4 mg/kg, i.p.) and evaluated for mechanical hyperalgesia. Previously, a time-effect curve was performed to verify the administration of EplEO and EplEO-βCD. In addition, the animals were evaluated for motor coordination and muscle strength using EplEO (50 mg/kg, p.o.), EplEO-βCD (50 mg/kg, p.o.), vehicle (isotonic saline, p.o.) or Diazepam (4 mg/kg, i.p.). After the experiments, the animals were sacrificed and evaluated for expression of Fos-positive cells in the spinal cord by immunofluorescence. EplEO produced a yield of 0.741% (m/m) and GC-MS/FID analysis identified 27 compounds in total, being (E)-cariophylene (14.16%), bicyclogermacrene (12.68%), 1,8-cineole (11.03%), α-pinene (6.79%) and β-pinene (5.10%) the majority. The complexation of EplEO-βCD by past complexation was shown to be more effective by the characterization tests. Treatment with EplEO-βCD produced a long-acting antihyperalgesic effect (p <0.05 vs. vehicle and p <0.05 vs EplEO) which had an effect time of eight hours when compared to EplEO (p <0.01 vs vehicle) with time effect of four hours, without changes in motor coordination or myorelaxant effect. In addition, EplEO and EplEO-βCD produced a significant antihyperalgesic effect (p <0.01 or p <0.001) over 7 consecutive days of treatment. The immunofluorescence assay demonstrated that the group of animals treated with EplEO had a significant (p <0.001) decrease in the number of Fos-positive cells in the spinal cord when compared to the vehicle group. In view of the foregoing, it has been demonstrated that the anti-hyperalgesic effect produced by EplEO has been improved following βCD complexation with a possible relationship in the classic central pain inhibition pathway.